Staged narrative : poetics and the messenger in Greek tragedy - Barrett, James, 1953- (Joan Palevsky imprint in classical literature., 2002)
The messenger who reports important action that has occurred offstage is a familiar inhabitant of Greek tragedy. A messenger informs us about the death of Jocasta and the blinding of Oedipus, the madness of Heracles, the slaughter of Aigisthos, and the de.